Surgical Treatment - Falconi, Massimo; Casetti, Luca; Salvia, Roberto; Sartori, Nora; Bettini, Rossella; Mascetta, Giuseppe; Bassi, Claudio; Pederzoli, Paolo (JOP. Journal of the Pancreas)
No abstract available. Image: G.B. Hospital. Verona, Italy